THE IMPORTANT ROOM OF SHALAT AS A BASIS FOR DETERMINING SPATIAL AND SPIRITUAL PATTERNS TO SHAPE CHILDREN'S CHARACTER - Ghoffar, Abdul; Mutammam Musthofa, Muhammad; Bashiroh, Ainin; Widya Agustin, Salsha; Nur Pribadi, Kharisma (Proceeding International Seminar of Islamic Studies, 2023)
Every Muslim must comply with Islamic law, and fear Allah SWT in order to be rewarded. Muslim family lifestyle is an important element in shaping children's Islamic behavior. Muslim families are obliged to regulate shalat times to shape the habits, behavior, and character of their residents.The author uses a study approach to discuss the concept of worship in Islamic thought, the importance of Islamic spatial patterns based on the Qur'an, the Sunnah of the Prophet, and the opinions of the ulama, taking into account the provisions in its implementation. The concept of spatial patterns through the shalat activity approach influences the design of Islamic family dwellings. Based on the above, the authors synthesize that early childhood education can be achieved through the application of architecturally oriented residential space patterns in shalat rooms.The results show that shalat is the most important starting point for Muslim families to build the character of their children. The availability of a shalat room, in addition to building an obedient personality, time discipline, hard work, and maintaining purity, also familiarizes the character with always remembering Allah SWT, living in balance, doing good, and loving peace.